TECHNOLOGICAL INNOVATION AND ENTREPRENEURSHIP FROM THE WESTERN AND ISLAMIC PERSPECTIVES - Adham, Khairul Akmaliah; Said, Mohd Fuaad; Muhamad, Nur Sa’adah; Yaakub, Noor Inayah (International Journal of Economics, Management and Accounting, 2013)
Extant theories of economic development and strategic management emphasize innovation and entrepreneurship in generating business profits and sustaining the industry toward achieving economic prosperity of a society. However, this domain of knowledge does not explicitly address the issues of social development and well-being in relations to innovation and entrepreneurship in the industries. This can mean neglecting social and moral development in the pursuit of economic development. To remedy this gap, this study brings in the Islamic worldview – an all-encompassing values-based view of life that embraces just economic and social development. The objective of this study is to provide a framework that conceptualizes innovation and entrepreneurship from an Islamic perspective. This study first discusses the concept of innovation and entrepreneurship from extant literature and then examines the concept from the Islamic perspective. In Islam, all conducts by members of organizations, including innovators and entrepreneurs, are tied to superordinate goals and conducted in accordance to the shariah and Islamic ethical standards as prescribed in the Qur’ân and Hadith. Such Islamic ethical dimensions, among others, emphasize the importance of akhlaq (good manners) of entrepreneur-managers, and their responsibility toward the well-being of the organization’s internal system as well as the society. All conducts when carried out earnestly (ikhlas with ihsan) form one’s ibadah, which are the acts of worshipping Allah. The conceptualization of Islamic perspective on innovation and entrepreneurship process supports the efforts of inventors and entrepreneur-managers to achieve worldly economic benefits that would ultimately enable them to attain the blessings of Allah (mardhatillah). Such superordinate orientations and value system, which address the issues of intentions and corresponding actions, enable the conduct of values-based innovation and entrepreneurship that achieve a balanced economic, social, and moral development. This perspective remedies the theoretical gaps and solves managerial problems that demand values-based endeavours in innovation and entrepreneurship.